Granuloma annulare of the external ear, a rare mimic of malignancy: two case reports - Haddad, Afaf (International Journal of Research in Dermatology, 2022)
Granuloma annulare (GA) is a granulomatous inflammatory largely cutaneous and less often subcutaneous condition with varied presentations ranging from localized to disseminated forms manifesting as erythematous papules or plaques affecting all ages and primarily involving the extremities. GA may affect other sites such as the face and cases limited to the orbit and ear are exceedingly rare. No consistent causative factor has been identified although there is an established association with diabetes mellitus, autoimmune diseases, infections, malignancies or localized trauma. The chief histological pattern of palisaded or interstitial granulomatous reaction is diagnostic, providing infections such as mycobacterium have been excluded. Standardized treatment is elusive and different modalities including local/intralesional steroids, cryo/photo/laser therapy or oral retinoids/antibiotics have been used with variable response. We report two cases of GA limited to the ear adding to the 13 previously published cases.